Hidup Sehat Bersama Al-Quran (Telaah Tematik Ayat-ayat tentang Kesehatan) - Qamar, Syamsul; Thulfitrah B, Nurlathifah; Ahmad, La Ode Ismail; Abubakar, Achmad (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Healthy Life with Al-Quran (Thematic Study of Verses about Health)This article aims to reveal the concept of healthy life with the Qur'an in maudhuiy interpretation approach which is a literary study. This article summarizes that explain of Qur’an and their correlation with hadith. He provides a comprehensive understanding that Islam really wants health and the impact it causes. Based on several verses and hadiths presented in this paper, there is a relationship between physical and psychological health, in which humans cannot be said to be healthy, when their minds are not healthy, when they are physically strong, they do not appreciate when they are mentally ill so that they are healthy mentally and physically. is the answer. To achieve quality health that combines body and soul, it is necessary to have a complete understanding of human self as a perfect entity if it does not separate aspects of the soul and body. When humans provide their bodily needs in the form of food and drink, the quality of what they consume will affect the quality of their soul.